Development of Fine Motor and Visual Motor Skills in Preparing Early Childhood Writing - Muhammad Arfan Mu’ammar; Mahrus Soleh; Afdol Awae (The Indonesian Institute of Science and Technology Research, 2023)
This research aimed to examine the process of fostering fine motor and visual motor skills in early childhood education. The study was conducted at PAUD Mambaul Ulum Bata-bata Pamekasan and employed a qualitative research approach using a combination of interviews, observations, and document analysis. The subjects of the research were managers, teachers, and assistants. The findings revealed that the development of fine motor skills was facilitated through the use of various media such as scissors, origami paper, blocks, and pencils. Additionally, the learning strategy was implemented through various methods such as lectures, demonstrations, assignments, and projects, utilizing media that was suited to the nature of each activity. The research also identified several key factors that supported the development of these skills, including the professionalism of educators, adequate infrastructure, and students' interest and enthusiasm for learning. However, the lack of sufficient numbers of accompanying teachers, an imbalance between the number of students and educators, and the absence of complete media and learning facilities were found to be inhibiting factors.